Uncertainty monitoring in Eurasian jays (Garrulus glandarius) - M. Loconsole; A. K. Schnell; E. Garcia-Pelegrin; N. S. Clayton (Animal Cognition)
Abstract Metacognition– namely the capacity to reflect on one’s own cognitive processes - provides animals with numerous evolutionary advantages. Metacognition abilities encompass enhanced decision-making in uncertain situations, more efficient resource management, error detection and correction, and improved problem-solving skills. Here, we investigate how Eurasian jays, Garrulus glandarius, monitor uncertainty through a working memory food-retrieval task. In this task, a desirable food item is hidden under one of two cups, which are then shuffled either once (easy treatment) or several times (difficult treatment). The jays then choose to either engage in locating the food or opt out by selecting a third cup that offers a less preferred food reward. Our findings reveal that the difficulty of the task significantly influenced the jays’ choice, with a higher tendency to opt out during difficult trials. Individual performance analysis revealed that when jays that typically opted out of difficult trials chose to engage instead, they exhibited significant accuracy. This suggests their decisions were guided by a confidence assessment of their knowledge. Overall, our study indicates that Eurasian jays possess metacognitive abilities that enable them to evaluate their own certainty and make strategic decisions based on perceived task difficulty and confidence in their knowledge. These capabilities likely confer advantages in natural settings, such as caching behaviours, allowing jays to make well-informed decisions about when to store or retrieve food based on environmental cues and internal assessments of uncertainty.